Navigating the fragmented landscape of online scholarly communication: a taxonomy of communication patterns - Ambrosj, Jacopo; Bordignon, Frédérique (2026)
Online Scholarly Communication (SC) is a vast and fragmented landscape difficult to navigate. Traditional core activities of SC, such as registration, certification, archiving, and awareness, have not lost their importance but have changed and been distributed across actors and venues. To bring clarity, we have developed a taxonomy of communication patterns of online venues for SC, i.e. the different ways in which online venues contribute to the core activities of SC for the units of SC they deal with. In this article, we present the taxonomy built on a corpus of 465 venues, and offer examples to illustrate its intended uses and analytical potential. Our taxonomy is a research tool to map the complex reality of SC. When combined with other methods such as analysis of discourse and economic models, it can produce sophisticated analysis of online SC.